Experimental investigation of CO2 uptake in CO2 hydrates formation with amino acids as kinetic promoters and its dissociation at high temperature - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Classen, Timo; Gatternig, Bernhard; Delgado, Antonio; Hitzmann, Bernd (Scientific Reports, 2022)
The dissociation of CO2 gas hydrates (GH) with amino acid kinetic promoters and without promoters was studied at a high temperature of 90 degrees C for a period of 20 min to understand the percentage of CO2 gas and to select the best promoter that aids CO2 gas entrapment along with stability at a high temperature. The possibility of using four hydrophobic food grade amino acids, namely cysteine, valine, leucine, and methionine, and one surfactant, lecithin, as kinetic promoters for CO2 GH has been studied. The amino acids were added 0.5 g (wt%), and lecithin was added 5 g for the GH production. Furthermore, the amino acids leucine and methionine gave some positive results, therefore, these amino acids were carried further for the experimentation purpose in the production of CO2 GH. Also, a combinational use of these amino acids was studied to investigate the effect on % CO2 retention in comparison to the normal GH. From the results, it was observed that the stability of GH decreases with an increase in temperature, but the addition of promoters, especially leucine + methionine + lecithin increased the CO2 uptake during GH formation.
CRIS-Team WoS Importer:2022-06-17